Impact of dentine hypersensitivity on oral health-related quality of life in individuals receiving supportive periodontal care - Goh, Victor; Corbet, Esmonde F.; Leung, Wai Keung (Journal of clinical periodontology, 2016)
Aim To determine the prevalence and impact of dentine hypersensitivity (DH) on oral health‐related quality of life (OHRQoL) in individuals receiving supportive periodontal care (SPC). Materials and Methods One hundred and two adults receiving SPC were recruited for a cross‐sectional study. Subjects were categorized into those who self‐reported DH (DH1) or did not (DH0). Impact of DH on OHRQoL was assessed using the Chinese Condition‐Specific Oral Impact on Daily Performance questionnaire (CS‐OIDP). Evaluation of DH included tactile‐stimulation followed by air‐blast, and recorded using a Visual Analogue Scale (VAS). Results Sixty‐one (59.8%) subjects self‐reported DH with mean air‐blast VAS score of 29.4 ± 21.3 mm and mean tactile‐stimulation VAS score of 10.9 ± 14.7 mm. Fifty (49%) subjects reported impact on OHRQoL (mean CS‐OIDP score = 4.7 ± 6.3). The most affected performance was cleaning the mouth (35.3%). Positive expression of DH and worse OHRQoL were associated with higher air‐blast and tactile‐stimulation VAS scores, and use of desensitizing agents. The minimally important difference (MID) in CS‐OIDP scores was 2.0 points. Approximately 30% of the subjects reported CS‐OIDP scores above the MID. Conclusions Dentine hypersensitivity affects OHRQoL in patients undergoing SPC. The extent of impact was associated with severity of DH.